2018
DOI: 10.1002/cben.201700017
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Hydrothermal Liquefaction for Biofuel and Biocrude Production from Microalgal Feedstock

Abstract: Microalgal biomass processing by continuous hydrothermal liquefaction (HTL) has recently received much interest and can be used to convert microalgal biomass to biocrude oil and drop‐in fuels. This review focuses on the conversion of microalgae biomass to energy production through continuous HTL processes. In addition, processes for upgrading feedstocks and biocrude are also discussed. The feed of the biomass slurry is treated according to size and moisture regulations. Following separation of the gaseous, liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…Continuous flow reactors (discussed in section ) have been developed for potentially continuous HTC, HTL, and HTG of biomass. ,,, However, the challenges remain in various stages of large-scale hydrothermal processes (i.e., selection and pretreatment of biomass feedstocks, optimization of continuous flow reactors, and separation and upgrade the bioproducts) . Specifically, continuous HTL and HTG have been explored for the hydrothermal treatment of lignocellulosic and nonlignocellulosic biomass (e.g., algae, sewage sludge, and food wastes). The following shortcomings still block the scale-up of HTL and HTG.…”
Section: Hydrothermal Treatment Of Biomass To Chemicals Fuels and Mat...mentioning
confidence: 99%
“…Continuous flow reactors (discussed in section ) have been developed for potentially continuous HTC, HTL, and HTG of biomass. ,,, However, the challenges remain in various stages of large-scale hydrothermal processes (i.e., selection and pretreatment of biomass feedstocks, optimization of continuous flow reactors, and separation and upgrade the bioproducts) . Specifically, continuous HTL and HTG have been explored for the hydrothermal treatment of lignocellulosic and nonlignocellulosic biomass (e.g., algae, sewage sludge, and food wastes). The following shortcomings still block the scale-up of HTL and HTG.…”
Section: Hydrothermal Treatment Of Biomass To Chemicals Fuels and Mat...mentioning
confidence: 99%
“…Mineral and trace element levels also vary among microalgae (2-20%) depending on the specific metabolic requirements and the availability in the mediums [38,39]. This ash fraction of the feedstock could later on interfere during the biomass conversion to biocrude and its further upgrading, and it could cause damage to the combustion system [40].…”
Section: Impact Of the Biomass Composition As A Biofuel Feedstockmentioning
confidence: 99%
“…produced from a wastewater treatment process. It has been reported that biomass with a high lipids content produces more bio-crude with respect biomass with higher proteins and carbohydrates content [63].…”
Section: Bio-crude Yieldsmentioning
confidence: 99%